Effect of Rice Storage Packaging with Basil Leaf Powder (Ocimum sanctum L.) Against Rice Weevil (Sitophilus oryzae L.) Attacks - Siti Aisyah; Dewi Fitriyanti; Helda Orbani Rosa (www.ulm.ac.id, 2024)
South Kalimantan BPS data (2022) shows that there has been a decline in rice production of 79.28 thousand tons (11.65%) so it is necessary to have rice suppliers from outside South Kalimantan to meet the rice demand target. Sitophilus oryzae is the main pest during the shelf life of rice. Controlling rice aphids can be done in various ways, including using appropriate storage media and applying vegetable pesticides to plants that are believed to be able to control them, one of which is basil. This research uses the factorial RAL method with 2 factors, namely packaging (W) and dose (D). The doses given are 0g, 10g, 14g, 18g. The packaging used is in the form of plastic containers and plastic sacks. Obtained 8 combinations, each repeated 3 times. So a total of 24 experimental units. The results of statistical analysis show that the combination of 18g of basil leaf powder in plastic packaging is the best treatment in suppressing the S. oryzae population with a mortality rate of 60%. During 30 days of observation, no new population growth was found and showed the lowest level of rice damage of 1.0% compared to other treatments.